6ER-028 Becoming an hospital pharmacist: an observational cross-sectional study on the educational pathways from students' perspective. (2nd March 2018) - Mengato, D; Langella, R; Rivano, M; Lamesta, C; Cancanelli, L; Confalonieri, C; Badiani, B; Pigozzo, S; Damuzzo, V
Abstract : Background: Despite the Common Training Framework project, routes to becoming an hospital pharmacist in Europe remain extremely patchy. Enrolment in a post-graduate Hospital Pharmacy School (SHP) is the way to become a hospital pharmacist in our country. Despite a harmonising effort that occurred in 2015, students still describe a heterogeneous real-life situation of SHPs between different universities, which results in learning difficulties and lack of scholarship. Purpose: The main purpose of our study is to evaluate, through the first national survey, the possible differences in the educational pathway of Italian SHP students. Material and methods: This is an observational cross-sectional students-oriented study. We investigated, through a questionnaire, five main topics: structure of residency training, study plan adherence, relationship between students and tutors, economic compensation and research activity. Results: Sixty-eight per cent (172/278) of national SHP students voluntarily participated in the survey. Eighty-seven per cent of residents regularly attended the rotation among assigned hospitals, but lessons' schedule frequently didn't fit with residency (66%). Students felt confident about drugs distribution, drugs' appropriateness and pharmacoeconomics, whereas they described poor competency in ethics committee, vigilance on community pharmacy, HTA and clinical trials. Despite this, the educational programme required a full-time residency, but only 24% of students received a scholarship funded by the university. An analysis of the remaining 76% described an uneven situation: 28% were employed by hospitals, 20% by community pharmacies, 6% worked out of the pharmaceutical field and 22% did not receiv any salary. Students receiving an academic scholarship attributed a statistically significant higher score to their education pathway compared to the other (p<0.001) and they published significantly more. Finally, we investigated the relationship between residents and tutors. In most cases this was satisfying except for students employed in community pharmacies. The perceived quality of tutoring was related to the degree of working independence of the resident (p=0.008). Conclusion: National SHPs still present a patchwork organisation and as long as an academic scholarship is not granted to all SHP students, the competing interests of employer institutions and academia may lead to important differences in training. Thus, we hope that our results encourage more investment in SHPs, in view of the growing responsibility of our profession. No conflict of interest